(untitled) (Journal of Global Accounting, 2022)
This study to empirically evaluates the effect of the adopted determinants on the cashholding behaviour of selected Commercial Banks in the pre and post recession period of Nigeria. Specifically, it intends to ascertain the extent to which Investing activities and Financing activities affect Cash holdings of Systematically Important Banks (SIBs) in the pre and post recession periods of Nigeria. It also intends to determine the extent of relationship between investments of SIBs in Nigeria and the volume of cash held in the pre and post economic recession periods. Secondary source of data collection was solely utilised, hence, the adoption of the ex-post facto research design. A total of seven (7) SIBs in Nigeria were purposively sampled, and extracts from their respective financial statements for the pre economic recession (2011 - 2014) and post economic recession (2015 – 2018) periods duly subjected to relevant analyses using Multiple regression and Spearman Correlation statistical tools. Findings obtained from analyses showed that Investing activities and Financing activities have significant effect on the Cash holdings of SIBs in the pre and post recession periods of Nigeria. It was also discovered that there is a significant relationship between investments of Systematically Important Banks in Nigeria and the volume of cash held by them in the pre and post economic recession periods. The study thus concluded that financial crisis may have changed the cash holding behaviour of SIBs and this is considered to have a long term effect. The study therefore recommends that Systematically Important Banks (SIBs) should be accorded reliable assistance by appropriate regulatory agencies into observing periodic self assessment of their cash holding choices towards ensuring that such decisions does not in anyway pose significant threat to the organisation’s going concern in the future. Also, given the magnitude of interest SIBs have in investment, renewed effort should hence be made at ensuring that such Investments are profitable ones pursued at manageable risk levels.